IDENTIFIKASI GEJALA STRES KLIEN DI YAYASAN RUMAH ORBIT SURABAYA SELAMA PROSES REHABILITASI - Sari, Nurma Yulya; Khusumadewi, Ari (Jurnal Bikotetik (Bimbingan dan Konseling: Teori dan Praktik), 2018)
Stress is a response to a person, both physically and psychologically to a change in the environment that is perceived to be disturbing and causing him/her to be threatened. To know someone experiencing stress need to know the symptoms of stress first. The background of this study was conducted to reduce the cases of suicide clients former drug users during the rehabilitation process. So it is necessary to know the symptoms of stress first. This study includes a type of literature study research by finding reference to the theory relevant to cases or problems found. Reference theory obtained by way of research literature study serve as the basic foundation and the main tool for research practice in the field. The study was conducted at the Orbit Healthy Home Foundation. Analysis of the results of research conducted by analyzing, comparing the standard of stress level with symptoms experienced by clients at the time of rehabilitation. The results showed that the client at Orbit Foundation Surabaya experienced stress at the third stage with symptoms of gastric disturbance was felt like an ulcer, muscle tension increasingly felt, feelings of unrest and emotional tension is increasing, disturbance of sleep patterns, body feels tired, easily sick.